Reflections on a shared leadership approach to curriculum development in higher education - Pienaar, Christo F; Raymond, Eileen B (South African Journal of Higher Education, 2016)
South African universities today must prepare teachers to meet the needs of diverse learners, including disabilities, linguistic differences, and extrinsic barriers to learning. This need was highlighted in the Education White Paper 6 which challenged South African schools to begin serving the needs of all learners, moving to an inclusive model and away from a segregated service model focused on deficits. This article was informed by a study in which we used a participatory action research model and an interpretative paradigm to analyse our learning about the challenges of effective leadership and about ourselves as co-leaders involved in curriculum development work. Based on the results, recommendations are made for faculty teams doing similar work in response to governmental policy initiatives. Keywords: leadership, teams, curriculum development, teacher education, inclusive education, Education White Paper